Political Rupture – the Unsolvable Dilemma of the Third Bulgarian State - Dimitrov, Aleksandar (Research Papers, 2019)
The political and economic problems and challenges faced by the Third Bulgarian State have been going on for 140 years. Such is the problem of the political rupture that has gripped Bulgaria in the years before and immediately after World War II. Its genesis, development and influence on our time deserve an in-depth political analysis. The article clarifies the notion of "political rupture", the typology of the phenomenon is proposed and special attention is paid to the contradictions it generates in Bulgarian conditions